The analysis of youth-related anglicisms among Bosnian youth - knowledge of their original form and meaning and attitudes towards them - Delić Haris; Dedović-Atilla Elma (ExELL (Explorations in English Language and Linguistics))
The importance of the English language in a contemporary globalized world leads to borrowing of English words into many languages, including Bosnian. The current research investigates the knowledge of the original English written form and translation of the English-origin youth-related words (anglicisms) among young native speakers of Bosnian. The study included 345 Bosnian and Herzegovinian high school students, both males and females, in 9 cities. The findings revealed that the usage of Anglicisms among Bosnian youth is not so frequent and that young people in Bosnia and Herzegovina are more familiar with the original written forms than with their translation/synonyms in the Bosnian language. Moreover, knowledge of these two forms of anglicisms shows variation only relative to a grade in English, while gender and age were found to be irrelevant. Also, no difference was shown in the knowledge of anglicisms in different fields: sports, fashion, and science and technology. Further research is recommended to study these and other youth-related anglicisms on a larger population sample.